Developing Engaging IPAS Lessons : Google Sites Learning Media Based on Banten Culture to Boost Interest and Learning Outcomes - Yuliani, Neni; Dewi, Ratna Sari; Leksono, Suroso Mukti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop Google Sites-based learning media that incorporates Banten cultural elements for teaching social and natural sciences, specifically focusing on cultural heritage material. The effectiveness of this media in enhancing students' interest and learning outcomes is also examined. This research employs a Research and Development (R&D) approach, utilizing the ADDIE framework, which comprises five key phases: analysis, design, development, implementation, and evaluation. The data sources for this study consist of students, teachers, and relevant documents. Data collection instruments include observation guidelines, interview protocols, questionnaires, and documentation sheets. Both qualitative and quantitative analysis techniques are used to examine the data. The results indicate that the validation of the Banten culture-based Google Sites learning material yields a score of 96%, categorized as 'Very Good'. The validation by media experts achieves a score of 88.33%, also categorized as 'Very Good'. Furthermore, the effectiveness test reveals an N-Gain value of 76% and a statistically significant difference between pretest and posttest scores (p < 0.05). These findings suggest that the Banten culture-based Google Sites learning media is effective in increasing students' interest and learning outcomes.